2021
DOI: 10.47836/pjssh.29.1.35
|View full text |Cite
|
Sign up to set email alerts
|

A thematic Review on Industrialised Building System (IBS) Publications from 2015-2019: Analysis of Patterns and Trends for Future Studies of IBS in Malaysia

Abstract: IBS has been theoretically and practically proven to improve the construction delivery apart from reducing the lead of time and cost throughout its supply chain. Under the Malaysian Construction Industry Transformation Programme (CITP) 2016-2020, it is stated that the government is accelerating the adoption of IBS through mechanisation and modern practices. Despite the government’s initiative, there have been relatively small amounts of materials published discussing the patterns in IBS publications in Malaysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…It is worth acknowledging that any non-systematic review must be systematic to some degree for credibility [59] (p. 5). Therefore, this paper adopted the thematic review approach that was introduced by Zairul [61][62][63] and conducted a thematic review in four steps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth acknowledging that any non-systematic review must be systematic to some degree for credibility [59] (p. 5). Therefore, this paper adopted the thematic review approach that was introduced by Zairul [61][62][63] and conducted a thematic review in four steps.…”
Section: Methodsmentioning
confidence: 99%
“…We adopted Zairul's [61][62][63] approach of using ATLAS.ti 9 software to extract and synthesize data. A thematic analysis procedure was conducted to construct themes over thorough reading on the subject [64].…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…This study used the thematic review approach with ATLAS.ti 9. the thematic review is a tool introduced by Zairul (2020Zairul ( , 2021, which was used because this research method applies the thematic analysis procedure in the literature review process. Clarke and Braun (2013) defined thematic analysis as the identification of the model and construction of themes during an in-depth reading of the topic.…”
Section: Methodsmentioning
confidence: 99%
“… Inclusion and exclusion criteria from Zairul (2021) for thematic review (TR). Reproduced with permission.…”
Section: Methodsmentioning
confidence: 99%
“…IBS is first experimented to cater to the housing demand such as Pekeliling Flats, Rifle Range Flats, and various more using numerous systems adopted from other countries like Germany, Japan, Dutch and United Kingdom (Al-Aidrous et al, 2021). The penetration of IBS in the Malaysian construction industry is well aligned to IR 4.0 and has gained a tremendous increase in research and practice; as it has various advantages such as faster project delivery, reduced amount of construction wastage at the site, fewer workers usage, minimize the total cost of construction (Dzulkalnine et al, 2018;Zairul, 2021) However, despite countless advantages of IBS adoption; the adoption rate is still low due to the resistance to change from the conventional method, lack of technology transfer, limited feasibility study of IBS application (Kamar et al, 2009) and the failure of early closed-fabricated systems (Din et al, 2012) of where Kamar et al (2012) concluded that the system was unsuitable with Malaysia's climate and social practise. A study conducted by Al-Aidrous et al, (2021), supports that the western system adopted has neglected the element of culture and climate that resulted in poor implementation of prefabrication industrialised construction and eventually caused the implementation to be somewhat unfavourable.…”
Section: Industrialised Building System (Ibs) Construction In Malaysiamentioning
confidence: 99%